The effect of Balassa-Samuelson in South-East Asia - Mohamad, Saadiah; Jusoff, Kamaruzaman; Nair, Mahendhiran; Zaghlol, Azlul Khalilah (Canadian Center of Science and Education, 2008)
High growth in the South-East Asian countries for the past three decades should imply high increases in productivity to reveal the Balassa-Samuelson (BS) effect of high growth accompanied by real exchange rate (RER) appreciation. This paper examines the effects of productivity increases by developing a robust unrestricted error correction model (UECM) of RER based on a class of theories of time-varying equilibrium exchange rates as opposed to the conventional PPP-based theory. An empirical study was carried out on four selected Southeast Asian countries: Indonesia, Malaysia, Singapore, and Thailand. This work suggests that the effects of productivity increases may be more complicated than what the theory suggests and points to the possibility that the Balassa-Samuelson is affected by the stage of economic development rather than mere productivity increases.